2014
DOI: 10.1007/s10534-014-9703-1
|View full text |Cite
|
Sign up to set email alerts
|

Gold complexes with benzimidazole derivatives: synthesis, characterization and biological studies

Abstract: Synthesis, characterization, DFT studies and biological assays of new gold(I) and gold(III) complexes of benzimidazole are reported. Molecular and structural characterizations of the compounds were based on elemental (C, H and N) and thermal (TG-DTA) analyses, and FT-IR and UV-Visible spectroscopic measurements. The structures of complexes were proposed based DFT calculations. The benzimidazole compounds (Lig1 and Lig2) and the gold complexes were tested against three Leishmania species related to cutaneous ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…These gold-based complexes with benzimidazole moieties as the ligands [49] showed antileishmanial antiparasitic activ- S6) and G2 indicated that the substitution of the benzimidazole scaffold at positions 1 and 2 was important.…”
Section: Activity Against Promastigotes and Amastigotesmentioning
confidence: 99%
See 1 more Smart Citation
“…These gold-based complexes with benzimidazole moieties as the ligands [49] showed antileishmanial antiparasitic activ- S6) and G2 indicated that the substitution of the benzimidazole scaffold at positions 1 and 2 was important.…”
Section: Activity Against Promastigotes and Amastigotesmentioning
confidence: 99%
“…These compounds (4 entries) showed significant activities against promastigotes and amastigotes of L. major, L. amazonensis, and L. braziliensis (Supplementary File 2, Fig. S6) [49]. Thirty-one entries relating toL.…”
Section: Search Of External Sourcesmentioning
confidence: 99%
“…Gold(I) and gold(III) complexes are also known to be effective against cutaneous leishmaniasis and malarial parasites . Gold complexes are known to be more effective on parasites than macrophages . Au(III) tetrachloride complexes are also reported to have anti‐HIV activity …”
Section: Figurementioning
confidence: 99%
“…Benzimidazoles are a class of organic compounds which possess extensive applications, especially in medicinal chemistry and a number of compounds containing a benzimidazole have been prepared and described with anti-inflammatory [1], anticancer [2], antimicrobial [3][4][5], antifungal [6], antiparasitic [7,8], and antiviral activities [9]. Benzimidazole-based metal complexes with luminescent properties [10][11][12][13] are also known.…”
Section: Introductionmentioning
confidence: 99%